2017
DOI: 10.1038/onc.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

EMP2 is a novel therapeutic target for endometrial cancer stem cells

Abstract: Previous studies have suggested that overexpression of the oncogenic protein epithelial membrane protein-2 (EMP2) correlates with endometrial carcinoma progression and ultimately poor survival from disease. To understand the role of EMP2 in the etiology of disease, gene analysis was performed to show transcripts that are reciprocally regulated by EMP2 levels. In particular, EMP2 expression correlates with and helps regulate the expression of several cancer stem cell associated markers including aldehyde dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies [40,41,42]. This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 88%
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies [40,41,42]. This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 88%
“…The proportions of ALDH high and CD133 +ve cells in the two endometrial cancer cell lines reported here are similar to those in other studies (42)(43)(44). This is the first study, however, in which the two populations of cells with cancer stem cell activity have been directly compared at a functional and genetic level.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, 38 critical genes in BRCA and 15 critical genes in KICH were significantly enriched in cell division ( p = 6.29E-08, Bonferroni correction) and DNA replication cell proliferation ( p = 5.40E-04, Bonferroni correction). The dysregulated miRNA-target gene pairs involved in these genes like miR-215/ SKA1 , miR-3653/ EMP2 and miR-192/ PIM1 , might enable the cells to evade normal constraints on cell proliferation [4547].…”
Section: Resultsmentioning
confidence: 99%